Disease Diagnosis Expert System In Palm Oil Plants Using Forward Chaining Method Android Based - Rezaldi firnando; Asnawati Asnawati; Jhoanne Fredicka (Jurnal Komputer, Informasi dan Teknologi, 2022)
Oil palm is one of the plantation types in Indonesia that occupies a position and is growing rapidly, whether it is owned by individuals or owned by companies. Along with the advancement of the times from time to time, where every time technology is always developing rapidly in the digital era. The purpose of this study is to provide information on oil palm plant diseases and appropriate and accurate countermeasures in maximizing the productivity of oil palm plants. The application of the forward chaining method to diagnose diseases of oil palm plants based on problems that arise in oil palm plants. Disease research in oil palm needs an expert system in analyzing diseases that arise in oil palm, therefore that productivity in oil palm plants can be fulfilled properly and get satisfactory results. The application built is online and can only be used by farmers who use smartphones.